2018
DOI: 10.12688/f1000research.14401.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of controlled type II diabetics ascending and descending a ramp surface at an imposed speed: A case-control study

Abstract: Patients with diabetes have been shown to suffer from Background: increased fall risk. Research shows that this risk is higher on irregular surfaces. Existing studies evaluate gait on irregular surfaces, such as stairs, asphalt, grass and stones. This study evaluates gait parameters in individuals with diabetes mellitus type II (DMII) with no history of peripheral neuropathy, while ascending and descending a ramp at an imposed speed, and compares them with healthy controls.Fifteen healthy volunteer participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Our study of cDMII participants ascending and descending a ramp did not yield any gait modifications distinguished to the control subjects (Rosario et al, 2018). However, those with cDMII exhibited a distinct standing posture instability while performing different challenging tasks, that increased in anterior-posterior sway when the vestibular (head movements) and somatosensory (standing on foam) systems were challenged, simultaneously (Rosario et al, 2020).…”
Section: Introductioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our study of cDMII participants ascending and descending a ramp did not yield any gait modifications distinguished to the control subjects (Rosario et al, 2018). However, those with cDMII exhibited a distinct standing posture instability while performing different challenging tasks, that increased in anterior-posterior sway when the vestibular (head movements) and somatosensory (standing on foam) systems were challenged, simultaneously (Rosario et al, 2020).…”
Section: Introductioncontrasting
confidence: 59%
“…The effect that DMII has on gait is known for individuals with uncontrolled blood glucose levels. Aside from our studies which have evaluated balance deviations, along with ascending and descending a ramp at an imposed speed, current literature is limited in published studies that investigate the gait of diabetic patients who are identified as having their glucose levels under control and are without known peripheral neuropathy (cDMII) (Rosario et al, 2020;Rosario et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the inclusion and exclusion criteria, as well as to ensure that the two groups were homogenous, all subjects utilized the same protocol implemented by Rosario MG, Orozco E, Babilonia N et al, (2018) that included, body mass index (BMI), standard anthropometric measurements and AHA/ACSM Health/Fitness (Balady et al, 1998) participation questionnaire.…”
Section: Subjectsmentioning
confidence: 99%
“…Due to the nature of the balance test and to ensure that participants could safely take part in this study, all subjects were further screened according to Rosario MG, Orozco E, Babilonia N, et al, (2018) clinical criteria. Additionally, the following was also performed as criterion:…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Subsequently, it showed impairment in the dynamic gait index, with an average of 19 +/± 5.45%, correlating with an increased fall risk. We consider the TA was recruited further to ensure toe clearance from the treadmill surface as the incline increased (Rosario et al, 2018(Rosario et al, , 2020. This prolonged activation can boost the endurance capabilities of said muscle.…”
Section: Discussionmentioning
confidence: 99%